Partial replacement of soybean meal with cottonseed meal in diets of broiler chicken sustains performance by upregulating the expression of nutrient transporter genes in small intestine - S. Haldar; S.S. Arora; A.K. Dhara; A. Debnath (Journal of Applied Poultry Research)
SUMMARY: This study investigated the effects of partially replacing soybean meal (SBM) with high-fibre cottonseed meal (HF-CSM) on performance traits and expression of certain nutrient co-transporter genes in the small intestine of male broiler chickens. The HF-CSM had lower CP and AME but higher EE, CF, NDF, and ADF compared to SBM. The free gossypol (FG) concentrations in the HF-CSM-containing diets were well below the limit (100 mg/kg) permitted by the European Union in complete chicken feed. Replacing up to 15 % of SBM in the diets of the experimental chickens with the HF-CSM had an insignificant (P > 0.05) effect on BW, FCR, or European Productivity Index at the time of harvest (42 d), and the 10 % replacement of SBM with HF-CSM (equivalent to 2.5 % inclusion of HF-CSM in the total ration) had effects similar to the all-SBM diet. Viscosity of jejunal digesta increased with the inclusion level of HF-CSM in diet when measured at 24 d (P = 0.048, linear effect) and 48 d (P = 0.001, quadratic effect). Inclusion of the HF-CSM upregulated the expression of nutrient co-transporter genes responsible for absorption of small peptides (PEPT-1), glucose and other hexose sugars (SGLT-1, GLUT-5), and amino acids (EAAT-3) in the small intestine at 24 d (P = 0.001, linear effect) and 42 d (P = 0.001, quadratic effect). Expression of PYY mRNA, associated with satiety regulation, increased with HF-CSM levels in diet at 24 d (P = 0.0001 linear effect) and 42 d (P = 0.001, linear effect), suggesting a potential anorexigenic effect. The study suggests that inclusion of HF-CSM by replacing 10-15 % of SBM on a weight-to-weight basis, which translates into 2.5–3 % inclusion of the former in the whole ration, may sustain the performance of broiler chickens